Black graduate education at historically Black colleges and universities : trends, experiences, and outcomes - Palmer, Robert T.; Hilton, Adriel A.; Boykin, Tiffany Fountaine (Emerald Publishing Limited : Information Age Pub., Inc., 2012)
This book provides context about the experiences of Black graduate and professional students attending HBCUs. Indeed, such research is important, particularly since HBCUs play a significant role in the number of Blacks who receive doctorates and professional degrees (i.e. M.D., D.D.S., J.D. etc.), especially in science and engineering. In fact, according to Redd and Minor (2008), the role of HBCUs in graduate education will become even more significant as more seek to offer graduate and professional programs, particularly at the doctoral level. This book focuses on the historical nature of graduate and professional education at HBCUs and the programs' contribution to society.Further, it provides context about the experiences of students who have attended these institutions for their post-baccalaureate pursuits. Finally, the book addresses the future of graduate and professional education at HBCUs and what fundamental aspects are needed to ensure their survival, competitiveness, and growth.This book appeals to faculty, departmental chairs, administrators, and students. Furthermore, higher education scholars, who conduct or have an interest in pursuing empirical research on Black graduate and professional education or the efficacy and relevance of HBCUs, will find this book useful given its unique and comprehensive approach focusing on supporting retaining, and graduating Black graduate students at HBCUs. In addition, this book is an invaluable teaching resource for faculty in Higher Education Administration, Student Affairs, or Sociology program.
Keywords: African Americans -- Education (Graduate); African Americans -- Education (Higher); African American universities and colleges -- Graduate work.; Universities and colleges -- United States -- Graduate work.; African American graduate students -- Social conditions.; Education -- Schools -- Levels -- Higher.; Relating to African American, Black American people.; Higher education, tertiary education.; elektronické knihy; electronic books